Principles of project finance - Yescombe, E. R. (Amsterdam ; Boston : Academic Press, 2002)
This introduction for practitioners offers a balanced view of project financing, integrating legal, contractual, scheduling, and other areas that participate in large multiparty projects, large single-asset purchases, and broad-based financing programs for fleets of assets. It mixes theories and case studies but avoids becoming too oriented toward applications in any one particular industry. It focuses on the concepts and techniques required by project finance people without being overly academic or beset by case studies. The author, who has a legal background, recognizes that some legal information is necessary, but he doesn't attempt to write a law book. Project Finance refers to the techniques of financing projects which are dependent on cash flows for repayment, as defined by the contractual relationships within each project. By their very nature, these types of projects rely on a large number of integrated contractual arrangements for successful completion and operation. Project finance is an element within the larger field of project management. Many organizations around the world utilize project management to enable innovative processes, to plan, organize, and control strategic initiatives, to monitor enterprise performance, to analyze significant deviations, and to forecast their impact on the organization and project(s). Project management can be found in many industries today, from construction and information systems to healthcare, financial services, education, and training. Key Features: -A comprehensive and authoritative guide to the theory and practice of project finance. -An international scope, covering projects in both the developed and developing worlds. -The book describes and explains: -Sources of project finance. -Typical commercial contracts (such as those for construction of the project and sale of its product or services) and their impact on the project finance structure. -Project finance risk assessment from the points of view of lenders, investors, and other project parties. -Structuring the project finance debt. -The key issues in negotiating a project finance debt facility. -Extensive glossary and cross-referencing. -No prior knowledge of project finance or financing techniques is assumed.on is also provided * Named among the Top 10 financial engineering titles by Financial Engineering News.
What is project finance? -- The project finance markets -- Project development and management -- Working with lenders -- Project contracts: (1) The project agreement -- Project contracts: (2) Ancillary contracts -- Commercial risks -- Macro-economic risks -- Political risks -- Political risk guarantees, insurance and finance -- Financial modelling and evaluation -- Financial structuring and documentation.
Ηλεκτρονικό βιβλίο
Keywords: Project management -- Finance; Electronic books